Using interactive multimedia to document and communicate Inuit knowledge - Gearheard, Shari (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractMedia technology has acted as both a threat to local knowledge and language, and a tool to strengthen it. More and more, indigenous peoples are using media for their own purposes from art to communication to education. Multimedia technology is surfacing as one useful tool in local knowledge and language revitalization efforts. Multimedia is being applied in a number of ways, preserving and passing on local knowledge and languages and showing potential for doing so in ways that engage young people and are more closely aligned with indigenous forms of teaching and learning. Discussing a case study example of one multimedia project in Nunavut, this paper evaluates multimedia in the context of documenting and communicating Inuit knowledge. Though there are challenges and issues to consider, multimedia and other technologies should be considered and creatively applied to help local people reach their goals. Texts and other forms of media remain important resources for documentation and communication in the North, but multimedia has the potential to grow into a key tool.